Comparative study of HbA1c and fasting plasma glucose vs the oral glucose tolerance test for diagnosis of diabetes in people with tuberculosis. Issue 6 (11th April 2017) - Aftab, H.; Ambreen, A.; Jamil, M.; Garred, P.; Petersen, J. H.; Nielsen, S. D.; Bygbjerg, I. C.; Christensen, D. L.
Abstract: Aim: To compare HbA1c and fasting plasma glucose assessment, with the 2‐h oral glucose tolerance test as reference, in screening for diabetes in people with turberculosis. Methods: Individuals ( N =268) with newly diagnosed smear‐positive tuberculosis were screened for diabetes at a tertiary hospital in Lahore, Pakistan. Diabetes diagnosis was based on WHO criteria: thresholds were ≥48 mmol/mol (≥6.5%) for HbA1c and ≥7.0mmol/l for fasting plasma glucose. Results: The proportion of participants diagnosed with diabetes was 4.9% ( n = 13) by oral glucose tolerance test, while 11.9% ( n = 32) and 14.6% ( n = 39) were diagnosed with diabetes using HbA1c and fasting plasma glucose criteria, respectively. The area under the receiver‐operating characteristic curve was 0.79 (95% CI 0.64 to 0.94) for HbA1c and 0.61 (95% CI 0.50 to 0.73) for fasting plasma glucose, with a borderline significant difference between the two tests ( P =0.07). Conclusions: HbA1c and fasting plasma glucose performed equally in terms of diagnosing new diabetes cases in individuals with tuberculosis, but the proportion of participants falsely classified as positive was higher for fasting plasma glucose. This may be explained by acute blood glucose fluctuations when using fasting plasma glucose. HbA1c may be a more reliable test in individuals with transient hyperglycaemia. What's new?: Very few studies and only one South‐Asian study have evaluated the performance of the two most common diagnostic variables, fasting plasma glucose and HbA1c, in screening for diabetes in people with tuberculosis. The present study is the first to compare HbA1c and fasting plasma glucose with the 2‐hour oral glucose tolerance test in people with smear‐positive tuberculosis in Asia. HbA1c performed better than fasting plasma glucose for detection of diabetes in people with tuberculosis.